Initial experience with percutaneous endoscopic gastrostomy with T-fastener fixation in pediatric patients - Kvello, Morten; Knatten, Charlotte Kristensen; Perminow, Gøri; Skari, Hans; Engebretsen, Anders; Schistad, Ole; Emblem, Ragnhild; Bjørnland, Kristin (Endoscopy International Open, 2018)
Background and study aims Insertion of a percutaneous endoscopic gastrostomy (PEG) with push-through technique and T-fastener fixation (PEG-T) has recently been introduced in pediatric patients. The T-fasteners allow a primary insertion of a balloon gastrostomy. Due to limited data on the results of this technique in children, we have investigated peri- and postoperative outcomes after implementation of PEG-T in our department.Patients and methods This retrospective chart review included all patients below 18 years who underwent PEG-T placement from 2010 to 2014. Main outcomes were 30-day postoperative complications and late gastrostomy-related complications.Results In total, 87 patients were included, and median follow-up time was 2.4 years (1 month – 4.9 years). Median age and weight at PEG-T insertion were 1.9 years (9.4 months – 16.4 years) and 10.4 kg (5.4 – 33.0 kg), respectively. Median operation time was 28 minutes (10 – 65 minutes), and 6 surgeons and 3 endoscopists performed the procedures. During the first 30 days, 54 complications occurred in 41 patients (47 %). Most common were peristomal infections treated with either local antibiotics in 11 patients (13 %) or systemic antibiotics in 11 other patients (13 %). 9 patients (10 %) experienced tube dislodgment. Late gastrostomy-related complications occurred in 33 patients (38 %). The T-fasteners caused early and late complications in 9 (10 %) and 11 patients (13 %), respectively. Of these, 4 patients (5 %) had subcutaneously migrated T-fasteners which were removed under general anesthesia.Conclusion We found a high rate of complications after PEG-T. In particular, problems with the T-fasteners and tube dislodgment occurred frequently after PEG-T insertion.